Upper Bound on Blocking Probability for Vertically Stacked Optical Banyan Networks with Link Failures and Given Crosstalk Constraint (Journal of Scientific Research, 2009)
Vertical stacking of multiple copies of an optical banyan network is a novel scheme for building nonblocking optical switching networks. The resulting network, namely vertically stacked optical banyan (VSOB) network, preserves all the properties of the banyan network, but increases the hardware cost significantly under first order crosstalk-free constraint. However, stringent crosstalk constraint may not always be necessary. Considering the fact that some designer may want to compromise the blocking probability and crosstalk constraint to a certain degree with the hardware cost, blocking behaviour of such VSOB networks have been analyzed to studying network performance and finding a graceful compromise between hardware costs and blocking probability under or without crosstalk constraint. In this paper, we present the simulation results for upper bound on blocking probability of VSOB networks with link failures and given degree of crosstalk constraint. We show how crosstalk adds a new dimension to the performance analysis on a VSOB networks. The simulation results presented in this paper can guide network designer in finding the trade-off among the blocking probability, the degree of crosstalk and the hardware cost in terms of vertical copies of banyan network in the presence of link failures.Keywords: Banyan networks; Blocking probability; Vertical stacking; Link-failures; Crosstalk.© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.DOI: 10.3329/jsr.v1i3.1191       J. Sci. Res. 1 (3), 484-494 (2009)